THE ROLE OF PROJECT MANAGERS IN CHANGE MANAGEMENT INITIATIVES - Kumar, Vijay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Organizations experience ongoing change due to various causes, including technological progress, market fluctuations, and changing client demands (Smith et al., 2018; Jones, 2020). Within this particular context, the significance of project managers in guiding and assisting change management projects becomes crucial. The convergence of project management and change management is a pivotal point for businesses aiming to not only endure but flourish in a swiftly altering commercial milieu (Turner & Müller, 2019). This study explores the various aspects of the project manager's function in the context of change management, with the goal of comprehending how project managers contribute to the success of change efforts and enhance organizational resilience.